PENGARUH PARENTING BERBASIS HADIS TERHADAP KARAKTER ANAK PADA KOMUNITAS KAJIAN MUSLIMAH DI KALIWATES JEMBER - Irfan Yuhadi; Nurul Budi Murtini (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2021)
Parenting encompasses everything related to the duties of parents in educating and raising their children. Hadith-based parenting is the parents’ skill in nurturing and educating their children based on the guidance of the hadiths of Prophet – peace and blessings of Allah be upon him. Every child has an inherent character realized into their behavior and actions. This research aims to examine the influence of hadith-based parenting on children’s character. The approach used in this research is a quantitative approach. The population of this research is the Kajian Muslimah community in Kaliwates Jember who are married and have at least 7-year-old children. The number of samples of 30 people were taken by simple random sampling technique. The instrument used is a questionnaire with a Likert scale. The data analysis technique used simple linear regression with the help of SPSS version 23. The result indicates that hadith-based parenting has a significant effect on children’s character in the Kajian Muslimah community in Kaliwates Jember. The significance of the influence of hadith-based parenting on children’s character in the Kajian Muslimah community in Kaliwates Jember is 41%.